Relationship between documentation method and quality of chronic disease visit notes - Neri, P.M.; Volk, L.A.; Samaha, S.; Pollard, S.E.; Williams, D.H.; Fiskio, J.M.; Burdick, E.; Edwards, S.T.; Ramelson, H.; Schiff, G.D.; Bates, D.W. (Applied Clinical Informatics, 2014)
Objective: To assses the relationship between methods of documenting visit notes and note quality for primary care providers (PCPs) and specialists, and to determine the factors that contribute to higher quality notes for two chronic diseases.Methods: Retrospective chart review of visit notes at two academic medical centers. Two physicians rated the subjective quality of content areas of the note (vital signs, medications, lifestyle, labs, symptoms, assessment & plan), overall quality, and completed the 9 item Physician Documentation Quality Instrument (PDQI-9). We evaluated quality ratings in relation to the primary method of documentation (templates, free-form or dictation) for both PCPs and specialists. A one factor analysis of variance test was used to examine differences in mean quality scores among the methods.Results: A total of 112 physicians, 71 primary care physicians (PCP) and 41 specialists, wrote 240 notes. For specialists, templated notes had the highest overall quality scores (p≤0.001) while for PCPs, there was no statistically significant difference in overall quality score. For PCPs, free form received higher quality ratings on vital signs (p = 0.01), labs (p = 0.002), and lifestyle (p = 0.002) than other methods; templated notes had a higher rating on medications (p≤0.001). For specialists, templated notes received higher ratings on vital signs, labs, lifestyle and medications (p = 0.001).Discussion: There was no significant difference in subjective quality of visit notes written using free-form documentation, dictation or templates for PCPs. The subjective quality rating of templated notes was higher than that of dictated notes for specialists.Conclusion: As there is wide variation in physician documentation methods, and no significant difference in note quality between methods, recommending one approach for all physicians may not deliver optimal results.Citation: Neri PM, Volk LA, Samaha S, Pollard SE, Williams DH, Fiskio JM, Burdick E, Edwards ST, Ramelson H, Schiff GD, Bates DW. Relationship between documentation method and quality of chronic disease visit notes. Appl Clin Inf 2014; 5: 480–490 http://dx.doi.org/10.4338/ACI-2014-01-RA-0007
Keywords: Clinical documentation; documentation quality; EHR; electronic documentation